2016
DOI: 10.1111/1749-4877.12200
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial differentiation in microhabitat use: Implications for reproductive isolation and ecological niche specification

Abstract: Niche differentiation enables ecologically similar species to coexist by lessening competition over food and/or shelters and may be critical for reproductive isolation between closely related species in close proximity. Because no extra traits need to evolve, spatial and temporal differentiation may readily take place to complement other isolating mechanisms. Two closely related treefrog species occur together in Korea: the endangered Hyla suweonensis and the widespread Hyla japonica. Advertisement calls are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 54 publications
0
41
0
2
Order By: Relevance
“…suweonensis produce advertisement calls at the center of flooded rice paddies, whereas male D . japonicus call from the banks of rice paddies, outside of water [54]. Such a niche segregation between the two species results in D .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suweonensis produce advertisement calls at the center of flooded rice paddies, whereas male D . japonicus call from the banks of rice paddies, outside of water [54]. Such a niche segregation between the two species results in D .…”
Section: Discussionmentioning
confidence: 99%
“…Dryophytes suweonensis is active at higher temperatures than D . japonicus [54], but it is not known whether these two species differ in basking behavior. Thus, despite D .…”
Section: Discussionmentioning
confidence: 99%
“…A tracking experiment showed that both treefrog species spent their days on rice paddy banks resting, hiding, and feeding28. Unlike natural ditches, concrete ditches typically remain dry, which limits grass growth.…”
Section: Discussionmentioning
confidence: 99%
“…In a lone semi-natural habitat for H. suweonensis , males of both species were calling at the edge of the wetland20. However, male H. suweonensis generally call in the middle of rice paddies and H. japonica males call at the edge of rice paddies22. The levee of rice paddies are typically composed of soils with grasses, which provide solid sites for calling treefrog males.…”
mentioning
confidence: 99%
“…Along this central ditch, and thus along the longest and straightest line available, usually runs a cemented lane, typically following the centre of the valley. In this study, ricepaddy complexes were considered spatially independent if further than 200 m apart, the maximum daily dispersion distance for the species (Borzée et al 2016a), or separated by landscape barriers impermeable to treefrogs (Roh et al 2014).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%